Aqueous 1, 3-dipolar cycloadditions promoted by copper nanoparticles in polydiacetylene micelles. Issue 13 (30th May 2017) - Clarisse, Damien; Prakash, Praveen; Geertsen, Valérie; Miserque, Frédéric; Gravel, Edmond; Doris, Eric
Abstract : A colloidal catalyst was assembled from copper nanoparticles to efficiently promote alkyne–azide cycloadditions in water. Abstract : A novel colloidal catalyst was developed through the encapsulation of cuprous oxide nanoparticles in polydiacetylene micelles. The Cu-based catalyst was applied to the Huisgen cycloaddition reaction in fully aqueous medium. The process neither requires heating nor a controlled atmosphere and the catalyst can be recycled in subsequent reactions without any loss of activity.